Customer Satisfaction of Surabaya Mortuary MUA Services - Muliatie, Yurilla Endah; Jannah, Nur; Panglipursari, Dwi Lesno; Sarie, Rena Febrita; Jum’ati, Nurleila (Jurnal Ilmu Manajemen Advantage, 2021)
The development of services is showing a significant increase. This is of course influenced by the complex and diverse needs of the community in an effort to meet their needs. The part of funeral services that cannot be ruled out is make-up services. Mortuary MUA may be a profession that is rarely heard of. This research aim was to determine whether customer experience influence on customer satisfaction in using the mortuary MUA services in Surabaya and also how the five dimensions of customer experience affect customer satisfaction. This study explains the causal relationship or influence between variables through hypothesis testing on certain samples. Population used is all consumers who use mortuary MUA services and the sample totally 60 respondents using Purposive Sampling method. The results shown that: there is a positive effect on the customer experience variable on customer satisfaction for mortuary MUA services in Surabaya. From the dimension of customer experience, it partially affects customer satisfaction and what is influential is the act dimension.